Gene Therapy and Down Syndrome: Can the future of Medicine bring a breakthrough? - Gondek, Katarzyna; Wojcieszek, Maria; Czarnota, Maksymilian; Gacka, Dominika; Fidelis, Magdalena; Żołnierek , Aleksandra; Mączyńska, Aleksandra; Szumlińska, Wiktoria; Alhuda Al-karawi, Noor; Kędziorek, Paulina; et al. (Journal of Education, Health and Sport, 2025)
Down syndrome (DS), or trisomy 21, is the most common chromosomal disorder, characterized by intellectual disability, congenital anomalies, and an increased risk of neurodegenerative diseases. This review synthesizes current knowledge on the etiology, clinical presentation, and modern therapeutic strategies for DS, including early intervention, medical management, and psychosocial support. Particular emphasis is placed on the revolutionary potential of CRISPR-Cas gene-editing technology as a tool for future treatment strategies. Drawing upon findings from many scientific publications, the article discusses the mechanism of CRISPR, its current medical applications, and its experimental use in silencing the extra chromosome 21 or correcting DS-associated genes. Technical, ethical, and delivery-related limitations are explored, alongside speculative but promising research directions, including base editing, prime editing, and cerebral organoids. The article concludes with a reflection on whether societal perceptions of genetic diversity should evolve alongside scientific innovation, highlighting that the greatest breakthrough may come not from altering genomes, but from fostering inclusion and understanding.